Complexity evolution quantification of bubble pattern in a gas-liquid mixing system for direct-contact heat transfer. (25th June 2018) - Xiao, Qingtai; Yang, Kai; Wu, Manman; Pan, Jianxin; Xu, Jianxin; Wang, Hua
Highlights: The pattern complexity of bubble swarms governs heat transfer performance of heat exchanger. A characteristic extraction technique for quantifying the complexity evolution is developed. Betti numbers was associated with image entropy, leading to measuring the mixture homogeneity. Abstract: The pattern complexity (kinetics and uniformity) of bubble swarms governs the heat transfer performance in gas-liquid contact systems such as direct-contact boiling heat transfer process. An image analysis technique is developed for quantifying the complexity evolution of bubble pattern in the gas-liquid contact system based on entropy theory and algebraic topology (more precisely, Betti numbers) using organic Rankine cycle direct-contact heat exchangers. The Betti numbers method is associated with image segmentation using entropy theory, leading to a useful model to characterize the homogeneity of the mixture. Experimental results show such an effectiveness. This novel method may be applied the study of a variety of multiphase flows.